Validity and Practicality of Student Worksheet Integrated by Sound Wave Experiment Set Using Smartphone with Sound Analyzer Basic 1.10.2 and Frequency Generator 2.6 Software - Putri, Yunita Jeliyah Jalis; Desnita, Desnita; Satri, Yulza (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2024)
The sound wave experiment in class XI high school physics learning did not go according to the planned mandate of the 2013 curriculum. Based on observations in five high schools, high school physics KITs are not yet complete and in numbers limited physics KIT. Based on the problems that occur in schools, there is a need for alternative media so that experimental activities can be carried out. Therefore, worksheets are needed that can guide students in carrying out sound wave experimental activities. This research uses a smartphone installed with Sound Analyzer Basic 1.10.2 software to measure the frequency and intensity level of sound as well as the Sound Generator 2.6 frequency as a sound source. The type of research used is research and development refers to the ADDIE model. Instrument of validity and practicality using a Likert scale. Validity results are calculated using the Aiken (1985) formula which is said to be valid if the value ranges between 0.87-1.00. Practicality results are calculated using a percentage technique according to Riduwan (2014) which is said to be practical if the value is 61%-80% and very practical 81%-100%. Students worksheets created are valid with an average value of content validity of 0.91, presentation validity of 0.92, and graphic validity of 0.88. Students worksheets created are practical with an average value of practicality according to students for ease of 87%, attractiveness of 87%, benefits of 85%, and an average value according to teachers for ease of 83%, attractiveness of 76%, benefits 79%.